Pengaruh Bukaan Separator Terhadap Kinerja Lalu Lintas di Jalan Perkotaan - Louise Elizabeth Radjawane (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2019)
One of solutions to reduce traffic problems on Jl.AP.Pettarani is the separation of paths based on their functions (fast and slow lanes) or called separators. The purpose of this study is to determine the performance of traffic at the separator openings, the effect of the length of the separator openings on the degree of saturation and braid velocity at the separator openings. The performance of the separator openings based on IHCM 1997 on Jl. AP.Pettarani (direction of Sultan Alauddin - Tol Reformasi) during the morning and evening peak hours are seen in the Bina Marga segment separator openings with each degree of saturation values of 2,054 and 2,113, the opposite direction, Mitsubishi segment separator has the greatest degree of saturation at morning peak hour and in the afternoon, 1,893 and 1,980 respectively. The addition of the length of the separator opening results in better weaving performance and the weaving speed will increase.